The central mechanisms of electroacupuncture at LR3 in the treatment of spontaneous hypertension: a PET and mRNA transcriptome study - Li, Jing; Peng, Chong; He, Kejie; Wang, Yumei; Lai, Xinsheng (Frontiers in Cardiovascular Medicine, 2024)
Objective: To reveal the efficacy and potential mechanisms of electroacupuncture(EA) in treating hypertension.Methods: Male spontaneously hypertensive rats (SHRs) were randomly assigned to the SHR group, EA group, and Sham-EA group, with Wistar-Kyoto rats (WKY) as the normal control group. SHRs in the EA group received electroacupuncture at the bilateral Taichong (LR3) acupoints for 7 consecutive days. Evaluation of systolic blood pressure(SBP), diastolic blood pressure(DBP), mean arterial pressure(MAP), and heart rate(HR) was conducted. Positron emission tomography-computed tomography (PET-CT) was employed to explore the active brain regions associated with acupuncture-induced blood pressure reduction. Furthermore, mRNA expression profiling was analyzed in the active brain regions to identify differentially expressed genes, and quantitative polymerase chain reaction (qPCR) was used to validate the mRNA expression of differentially expressed genes in the active brain region.Results: EA reduced elevated SBP, DBP, MAP and HR in SHR. PET-CT revealed that EA decreased glucose metabolism in the hypothalamus. Genomic analysis suggested that, compared to the SHR group, the differentially expressed genes in the hypothalamus of the EA group included Nr4a1, Sirt1, Trh, GPR88, Cck, and Th. EA downregulated the mRNA expression of Th, Trh, Gpr88, and Nr4a1, while upregulating the expression of Sirt1 and Cck at the mRNA level.Conclusion: EA may exert a unique antihypertensive effect in the hypothalamus of SHR, involving the modulation of sympathetic nerve activity, neuroinflammation, and oxidative stress response.